Influence of airline ownership rules on aviation policies and carrier strategies - Chang, Y-C. (Cranfield University, 2002)
Airlines are not able to conduct their businesses in the same way as other global transnational industries. They are inhibited by the foreign ownership restrictions in Air Services Agreements and national laws. Since the United Kingdom and the United States signed the first Bermuda agreement in 1946, the nationality clauses contained in virtually all bilaterals have limited the companies designated to provide services to those airlines owned and managed by nationals of the respective countries. A key reason why foreign ownership rules remain in place is that they protect national airlines. In doing so, they also limit the strategies available to governments whose carriers are in difficulties. The 57 years old bilateral system restricts the development of international air services, adversely affecting airlines and their users- travellers and the tourism and air freight industries. As time goes on, the rapidly changing air transport environment of privatisation, liberalisation and globalisation is forcing airlines to seek structural adjustments in order to survive in the new millennium. Airlines are asking to have more freedom for their strategies, in order to enhance their profitability. Pressures have been growing to ease the ownership rules contained in bilateral agreements to allow airlines greater commercial freedom. As there is no comprehensive research on the topic, this study aims to provide a detailed analysis of the impact of airline ownership rules. It will provide a point of reference for organisations like ICAO and nations to review the ownership issue in the future. This research starts with a review of the historical background, the current limitations in different countries and the pros and cons of ownership rules. It analyses how aviation markets have been influenced to date around the world and how governments and carriers have responded to these influences. It goes on to identify the main benefits and risks of foreign investment, and the motives for foreign investment in the EU and Asia- Pacific. It assesses the prospects for change in ownership rules under multilateral and plurilateral proposals, and develops a strategy for changing the current ownership rules. It concludes by predicting how airlines will react to such changes and makes suggestions for European Airlines in the Asia-Pacific region.